Reply to discussion on 'Palaeogeographical evolution of the Rattray Volcanic Province, Central North Sea', by Qurie et al. 2020 (JGS, 177, 718–737). Issue 3 (May 2021) - Quirie, Ailsa K.; Schofield, Nick; Holford, Simon P.; Jolley, David W.; Archer, Stuart G.; Hole, Malcolm J.; Hartley, Adrian; Watson, Douglas; Burgess, Roger; Pugsley, Jessica H.; Underhill, John R.
No abstract available